Improving Elementary School Students' Conceptual Understanding in Islamic Education Learning with the Numbered Head Together Model - Saifullah (MANDAILING GLOBAL EDUKASIA, 2025)
Teachers must use a variety of learning models to facilitate the achievement of learning objectives. This study aims to improve the ability to understand the concept of elementary school students in Islamic education learning. The type of research used in this study is classroom action research. The research design used is the Kemmis and Mctaggart model with 4 steps, namely planning, action, observing and reflection. The subjects of this study were fifth grade elementary school students. The data collection techniques used were observation and tests. The data obtained were then analyzed using descriptive statistical techniques. The results of the study showed that there was an increase in students' ability to understand the concept of Islamic education learning using the Numbered Head Together model. This is evidenced by the average class in the pre-cycle was 60.73, cycle one 75.67 and cycle two 82.39. Furthermore, the percentage of completeness also showed an increase, namely pre-cycle 53.47%, cycle one 69.33% and cycle two 89.75%. Based on these results, the Numbered Head Together model can be used as one of the solutions to overcome the problem of students' understanding of the concept of Islamic education learning in elementary schools.